Mucosal alpha-papillomaviruses are not associated with esophageal squamous cell carcinomas: lack of mechanistic evidence from South Africa, China and Iran and from a world-wide meta-analysis - Halec, Gordana; Schmitt, Markus; Egger, Sam; Abnet, Christian C.; Babb, Chantal; Dawsey, Sanford M.; Flechtenmacher, Christa; Gheit, Tarik; Hale, Martin; Holzinger, Dana; Malekzadeh, Reza; Taylor, Philip R.; et al. (International journal of cancer, 2016)
Epidemiological and mechanistic evidence on the causative role of human papillomaviruses (HPV) in esophageal squamous cell carcinoma (ESCC) is unclear. We retrieved alcohol- and formalin-fixed paraffin-embedded ESCC tissues from 133 patients seropositive for antibodies against HPV early proteins, from high-incidence ESCC regions: South Africa, China and Iran. With rigorous care to prevent nucleic acid contamination, we analyzed these tissues for the presence of 51 mucosotropic human alpha-papillomaviruses by two sensitive, broad-spectrum genotyping methods, and for the markers of HPV-transformed phenotype: (i) HPV16/18 viral loads by quantitative real-time PCR, (ii) type-specific viral mRNA by E6*I/E6 full-length RT-PCR assays and (iii) expression of cellular protein p16INK4a. Of 118 analyzable ESCC tissues, 10 (8%) were positive for DNA of HPV types: 16 (4 tumors); 33, 35, 45 (1 tumor each); 11 (2 tumors) and 16, 70 double infection (1 tumor). Inconsistent HPV DNA+ findings by two genotyping methods and negativity in qPCR indicated very low viral loads. A single HPV16 DNA+ tumor additionally harbored HPV16 E6*I mRNA but was p16INK4a negative (HPV16 E1 seropositive patient). Another HPV16 DNA+ tumor from an HPV16 E6 seropositive patient showed p16INK4a upregulation but no HPV16 mRNA. In the tumor tissues of these serologically preselected ESCC patients, we did not find consistent presence of HPV DNA, HPV mRNA or p16INK4a upregulation. These results were supported by a meta-analysis of 14 other similar studies regarding HPV-transformation of ESCC. Our study does not support the etiological role of the 51 analyzed mucosotropic HPV types in the ESCC carcinogenesis.
First published: 03 November 2015
Gesehen am 10.09.2020